Causes of maternal death in Mizan Aman and Gebretsadik shawo general hospitals from 2011 – 2015: A case - control study using propensity score matching analysis - kahsay, tensay; Legese, Tegene; Mulatu, Kebadnew (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To identify causes of maternal death in Mizan Aman and Gebretsadik shawo general hospitals Methodology: A case control study on 595 charts, 119 cases and 476 controls was conducted in Mizan Aman & Gebretsadik shawo general hospitals. Data was analyzed by STATA 13.1. Propensity score matching analysis was used to see causes of maternal death. Results: Hemorrhage were the main direct causes of maternal death which accounts 47.9% (β =0.58 (95% CI (0.28,0.87)) in hospital but when projected to population based the sample (β =0.26 (95% CI (0.22,0.31)). Followed by infection 36 (25.21%) (β = 0.50 (95% CI (0.08, 0.92)). when projected to population based the sample PIH 7.6%) is significant cause (β = 0.16 (95% CI (0.13, 0.19). Most death (74.8%) occurred during post-partum period. Recommendation: The health professionals must work on awareness creation on early arrival at health institution for delivery before development of different complications